Prenatal diagnosis and management of a giant intrahepatic arteriovenous malformation—Sonographic findings, clinical implications, and treatment. Issue 8 (3rd August 2022) - Walter, Adeline; Calite, Elina; Müller, Andreas; Kalff, Jörg C.; Meyer, Carsten; Geipel, Annegret; Gembruch, Ulrich; Schreiner, Christine
Abstract: Prenatal detection of complex giant hepatic arteriovenous malformation requires an examination of the affected fetal hemodynamic situation with emphasis on the affected arterial supply pattern. Early pediatric surgeon presentation is needed, as timely surgical intervention appears to be essential.